Through the keyhole: Ethnographic analysis of cyber violence in Egypt - Fouda, Radwa (AUC Knowledge Fountain, 2019)
Internet has long existed in Egypt, however sudden scholarly interest came after the 2011 revolution. The global scholarly body tended to couple internet accessibility to the so-called Arab-spring, without studying the other forms and politics of internet as an evolution, and almost none have delved in the dungeons of Cyber violence in the MENA Region, needless to say in Egypt. It focuses mainly on individual-to-individual perpetration of violence, how, when and why people variably define unsolicited intervention with their data as "violence", and how, when and why, they choose other notions to define such incident(s). By doing so, it opens up questions about notions such as surveillance, privacy, kinship, control and care, sovereignty, legibility, legitimacy, marginalization and rights. The structure is seen as a vertical gradient, each chapter is a dominant colour that seeps into the one the follows. While cyber violence is visualized as a circular gradient that floods into the center, while having nodes of colours around the edges that signify the prominent hue of the violence perpetuation and the effects of other nodes on its hue. While this thesis is premised primarily on the Castellian view of the network society, various other scholars constitute the rest of the pillars of this thesis to engage more with notions of the state, the social, capital, violence, technology. From Weber, Deleuze, Das, Tilly, Arendt, and Fanon, to Haraway, Bernal, Spivak, Latour and McLuhan, these theories try to give justice to the multitude of entanglements produced by the 9 interlocutors whose stories are extremely rich and telling. From Family, to friends, to work managers, to intimate partners, to totally anonymous persons; the perpetration of violence varying in justifications between care and control, have illustrated the Chimeras that our cyber selves are. Through engaging and living the ups and downs with my interlocutors, I have come to realize the complexities that violence studies involve, beside those that Internet analysis have, through interviews, side talks, countless private messages, and cyber security measures, I have also understood the levels upon which social-scientists deal with their data, as well as themselves in the data, and how interlocutors and the social handle them.